PHENOMENON OF DEMIKHOV. At N.V. Sklifosovsky Institute (1960–1986). V.P. Demikhov and his experiments in the field of organ transplantation in 1969–1970 - S. P. Glyantsev; Yu. A. Shabunts (Трансплантология (Москва))
With the involvement of archival documents, the results of research performed by V.P. Demikhov and the employees of the Organ Transplantation Laboratory at the N.V. Sklifosovsky Research Institute for Emergency Medicine (further – Institute) in 1969–1970 have been analyzed. At that time, under V.P. Demikhov's guidance and his personal participation, the Laboratory carried out the following developments: (1) an anatomical method of heart and lung transplantation in experiment and on human cadavers; (2) a method of revitalizing the heart and the whole human body using direct cardiac massage and a portable mechanical heart connected to auricles; (3) the method of liver transplantation in experiment and its anatomical rationale for clinical implementation in liver failure; (4) a method for assessing the function of a transplanted heart using electrocardiography; (5) the method of transplantation of the small intestine fragments; (6) a method of transplanting the pancreas, isolated or in combination with the duodenum and liver, to the renal vessels; (7) a method of replanting the cardiopulmonary complex on peripheral vessels for the treatment of terminal cardiopulmonary insufficiency, and a number of others. For experimental studies, the methods of an anatomical X-ray investigation of the main vessels and X-ray vasography of a transplanted heart were used. For heart transplantation, V.P. Demikhov's anatomical technique and biatrial Lower-Shumway technique were applied. To conduct a series of studies, V.P. Demikhov managed to attract large third-party organizations: the Krasnoyarsk Research Institute of Physics of the Siberian Branch of the USSR Academy of Sciences (creation of a mechanical heart), the Pyatigorsk Machine-Building Plant (creation of a portable thermostat to preserve revitalized organs), Central Research Institute of Tuberculosis of the Ministry of Health of the USSR (development of a method for implanting a cardiopulmonary complex to peripheral vessels), Research Institute of Poliomyelitis (operations on monkeys). We emphasize that all methods developed were recommended by the author for their implementation in clinic. A list of operations performed in the organ transplant laboratory in 1969–1970 is given. Most of the operations performed were transplantations (implanting) of the cardiopulmonary complex, isolated heart, and cadaveric heart revitalizations. It was noted that, in addition to the Research Topics included in the Working Plan of the Institute, V.P. Demikhov developed many individual, search topics, including transplantation of halves of the body, head, liver, uterus, kidney, and sternum. All of them, after their completion, were planned for implementation in the clinic.